PEMODELAN REGRESI SPASIAL INVESTASI LUAR NEGERI YANG MASUK KE INDONESIA - Susila, Muktar Redy; Putri, Rizfanni Cahya; Arini, Dian (PATTIMURA UNIVERSITY, 2020)
One of the important factors in the growth of a country's economy is investment. Sources of investment are divided into two, namely foreign investment and domestic investment. There are many benefits of foreign investment. These benefits are such as for development, employment, tax revenue, increasing foreign exchange, international trade, strengthening friendship with foreign countries and much more. The purpose of this research is to modeling of foreign investment in Indonesia using spatial regression. The predictor variables used are the number of labor and the net monthly salary. Based on the results of research analysis obtained information that the West Java province is the highest province to get investment funds from abroad. The highest net monthly salary in Indonesia is DKI Jakarta province. The highest number of labor in Indonesia is West Java Province. Based on the results of the Lagrange Multiplier test which showed a significant Lagrange Multiplier (lag) with a p-value < Î± = 5%. That's shows for the number of labor, the net monthly salary, and the foreign investment in Indonesia fulfill the spatial dependencies assumption. Based on the spatial regression model shows the number of labor, the net monthly salary, and the weighting has a significant impact on foreign investment in Indonesia.